The role of polyamines in regulating amino acid biosynthesis in rice grains. (9th June 2021) - Xu, Yunji; Jian, Chaoqun; Li, Ke; Tian, Yinfang; Zhu, Kuanyu; Zhang, Weiyang; Wang, Weilu; Wang, Zhiqin; Yang, Jianchang
Abstract: Polyamines (PAs) are important endogenous plant growth regulators mediating the grain yield and quality in rice. This study was to clarify whether and how PAs regulate amino acid composition and content in milled rice. We grew three categories of rice cultivars differing in protein contents in the field and investigated the relationship of free‐PAs concentrations in filling grains with the activities of key enzymes involved in amino acid biosynthesis and with the amino acid contents of milled rice. Cultivars with higher concentrations of free‐Spermidine (Spd) and free‐Spermine (Spm) exhibited higher amino acid contents than the others. The concentrations of free‐Spd and free‐Spm were significantly and positively correlated with the contents of essential amino acids (EAAs), non‐essential amino acids (NEAAs), and total amino acids (TAAs) in milled rice, whereas the concentration of free‐Putrescine (Put) had no effect on these parameters. The concentrations of free‐Spd and free‐Spm were linearly associated with the activities of glutamine synthetase (GS), glutamate synthetase (GOGAT), aspartate transaminase (AST), aspartate kinase (AK), and alanine transaminase (ALT), but only GOGAT, AST, and ALT were significantly and positively correlated with amino acid content. The application of exogenous Spd or Spm to panicles increased the activities of these key enzymes and amino acid contents, whereas the application of MGBG (an inhibitor of Spd and Spm synthesis) had the opposite effect. Applying Put had no significant effect on these traits. These results suggest that free‐Spd and free‐Spm enhance amino acid biosynthesis during grain filling in rice, primarily by improving the activities of GOGAT, AST, and ALT. Abstract : Cultivars with higher concentrations of free‐Spermidine (Spd) and free‐Spermine (Spm) exhibited higher amino acid contents than the others. The concentrations of free‐Spd and free‐Spm were significantly and positively correlated with the contents of essential amino acids (EAAs), non‐essential amino acids (NEAAs), and total amino acids (TAAs) in milled rice, whereas the concentration of free‐Putrescine (Put) had no effect on these parameters. The free‐Spd and free‐Spm could enhance amino acid biosynthesis in rice grains, primarily by improving the activities of GOGAT, AST, and ALT.